MENAFSIR LGBT DENGAN ALKITAB - John Mansford Prior (Jurnal Ledalero, 2020)
In his latest book the biblical theologian Gerrit Singgih looks in detail at verses in the Bible about same sex relationships that ring negative and also the few more positive examples of same sex relations. This article contrasts Singgih’s exegesis with that of Rome, both in documents from the Congregation for the Doctrine of the Faith and in the Catechism of the Catholic Church, and also in the Catechism of the Indonesian bishops. Rome states that finding oneself with “homosexual tendencies” is morally neutral while also declaring it “objectively bad.” According to Rome every sexual act has to be open to life and so homosexual relations are sinful. However, this is demonstrably wrong, as for instance, for infertile or elderly married couples. The writer concludes that he is in full agreement with Gerrit Singgih who interprets the negative verses in the Bible within the context of biblical times.  Keywords: LBGTQ+, Hermenutic Pattern, Creative Interpretation, Neutral Status, Natural Law.